STUDENTS' HABIT IN READING NEWSPAPERS AND THEIR VOCABULARY MASTERY: A CORRELATIONAL STUDY - Indah sari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study is aimed to know the correlation between students’ habit in reading newspapers and their vocabulary mastery, and also to discovery the profile of students’ habit in reading newspaper and their vocabulary mastery. This research used correlation design with quantitative approach. The participant of this study are 15 students of intermediate level of FLDI Nurul Jadid Islamic Institute. A questionnaire that consist of 22 items was used to collect the data of students’ habit in reading newspaper and a test to know their vocabulary mastery. The first finding of this study shows there is a correlation between students’ habit in reading newspaper and their vocabulary mastery, and it is correlates at 0.59 which means the correlation is in moderate correlation category. This study also shows the students’ habit in reading newspapers has high level with mean value at 4.00. Furthemore, the students’ vocabulary mastery is in the very high category. Keywords: Correlation, Reading Habit, Vocabulary Mastery, Newspapers